Getting It Done: A Guide for Government Executives - Wagner, Martin G.; Abramson, Mark A.; Breul, Jonathan D.; Kamensky, John M.; Chenok, Daniel J. (Rowman & Littlefield Publishers, 2013)
Getting It Done was written for those who have answered the call to public service. Now, in this revised edition, the editors of IBM’s Center for The Business of Government series have assembled a comprehensive guide to navigating the current environment of government, and what government leaders ought to know to survive and thrive with respect to the ways it’s evolved over the years. Concise analyses of the roles and responsibilities of those involved in any political decision accompany informative and instructional chapters, each highlighting a key step any public servant must take to ensure they do all they can for the people and causes they represent. From the patient and careful study of an issue, to the assembly of a trusted advisory team and the development and execution of a focused vision and agenda, leaders of all kinds will find some part of this book to incorporate into their own leadership strategies, for which this book’s expert and pragmatic insights prove a refreshing boon.